2009
DOI: 10.1104/pp.108.133520
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Profiling of Starch Biosynthesis and Degradation in the Developing Barley Grain  

Abstract: Barley (Hordeum vulgare) grains synthesize starch as the main storage compound. However, some starch is degraded already during caryopsis development. We studied temporal and spatial expression patterns of genes coding for enzymes of starch synthesis and degradation. These profiles coupled with measurements of selected enzyme activities and metabolites have allowed us to propose a role for starch degradation in maternal and filial tissues of developing grains. Early maternal pericarp functions as a major short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
157
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(171 citation statements)
references
References 87 publications
(118 reference statements)
14
157
0
Order By: Relevance
“…7). As reported earlier (Sun et al, 1998;Burton et al, 1999;Radchuk et al, 2009), the transcripts of HvSBEIIb and HvLD were mainly found in the endosperm and are thus likely to be involved in the biosynthesis of storage starch (Table I; Fig. 8).…”
Section: Diurnal Regulation Of Starch Metabolism and Sugar Signalingmentioning
confidence: 54%
See 4 more Smart Citations
“…7). As reported earlier (Sun et al, 1998;Burton et al, 1999;Radchuk et al, 2009), the transcripts of HvSBEIIb and HvLD were mainly found in the endosperm and are thus likely to be involved in the biosynthesis of storage starch (Table I; Fig. 8).…”
Section: Diurnal Regulation Of Starch Metabolism and Sugar Signalingmentioning
confidence: 54%
“…9; Supplemental Table S7). This observation lends support to a role of HvBAM5 in the degradation of transitory starch during the night with granular starch and/or linear maltodextrins as substrate (Fulton et al, 2008;Radchuk et al, 2009). Moreover, activation of HvBAM5 by Suc starvation at the end of the night contrasted to the activity of genes involved in the initial metabolism of Suc, such as HvCWINV1, HvSUT2, and HvSTP1 (Fig.…”
Section: Diurnal Regulation Of Starch Metabolism and Sugar Signalingmentioning
confidence: 79%
See 3 more Smart Citations